On the composition of Sr₂Fe₁.₅Mo₀.₅O₆₋δ – Sm₀.₂Ce₀.₈O₂₋δ composite as fuel electrodes for hydrogen reversible solid oxide cells - Li, Hao-Yang (2023)
Sr2Fe1.5Mo0.5O6-δ-Sm0.2Ce0.8O2-δ (SFMO-SDC) composites are high-efficiency fuel electrode materials for reversible solid oxide cells (rSOCs). Systematic variation in the SFMO-SDC composite shows that the composite with 40 wt% of SDC gives rise to the highest amount of oxygen vacancy and the highest number of electronic defects due to multiple electronic activation effects. Polarization resistance changes over the steam content show the parabolic trend with the optimal humidity at 20 vol% at open circuit voltage and in fuel cell mode, while in electrolyzer mode, highly humidified hydrogen is favored. Electrochemical studies and distributions of relaxation times analysis illustrate that the rate-determining step in fuel cell mode is the water desorption reaction whereas that in electrolyzer and at open circuit voltage (OCV) is surface chemical diffusion/oxide transport processes.